Exploring Co-Presence in Virtual Work: A Literature Review - Sarwesti; Nanda Amalia Putri; Martina Piranti; Dian Ariani; Irwansyah (PERSPEKTIF, 2023)
In recent decades, virtual work has emerged as a prominent paradigm in the world of employment. Within discussions surrounding virtual work, the concept of co-presence has garnered significant attention. Co-presence facilitates virtual workers to feel integrated into their teams and fosters relationships with colleagues. This research undertakes a comprehensive literature review to delve into the concept of co-presence, its crucial determinants, and the implications it holds. A total of 34 journal articles were scrutinized for inclusion based on their alignment with the research topic. The synthesis of these studies reveals that co-presence plays a pivotal role in supporting virtual work. Furthermore, the alignment of co-presence technology with job characteristics emerges as a critical consideration to ensure technology enhances rather than hinders productivity.